Membangun Kesadaran Ekologis melalui Penyuluhan Hukum tentang Pengelolaan Hutan di Desa Girisekar, Gunungkidul - Fakultas Hukum Universitas Negeri Surabaya; Nabilla Desyalika Putri; Tamsil .; Indri Fogar Susilowati; Mahendra Wardhana; Sri Budi Purwaningsih (Fakultas Hukum, Universitas Negeri Surabaya, 2025)
Indonesia has extensive and strategic forest areas, but managing them remains challenging, mainly due to limited community knowledge of forestry laws. This community service program was conducted in Girisekar Village, Gunungkidul, to improve legal and ecological awareness through legal counseling focused on village and community forest management. The approach used was legal counseling with a juridical-empirical method, involving 25 participants from diverse social backgrounds. The pre-test results showed that most participants were unfamiliar with the latest forestry regulations, the status of customary forests, or the requirement to register community forests. However, they had a basic understanding of technical management through social forestry groups. After the counseling session, the post-test indicated a significant increase in knowledge about community forest management (from 50% to 73%) and the rights and obligations of managers (from 35% to 80%). While understanding of statutory regulations remained unchanged, the activity successfully facilitated important dialogue between the community and resource persons and also strengthened ecological awareness. This activity significantly advances legal development by promoting practical understanding and community involvement in sustainable forest governance. The recommendation is to maintain ongoing, structured legal counseling programs and to enhance village institutions so they can efficiently manage, store, and market forest products. Therefore, legal counseling is not just a temporary activity but a strategic tool for fostering an adaptive, just, and community-focused legal culture.